2014
DOI: 10.1038/onc.2014.372
|View full text |Cite|
|
Sign up to set email alerts
|

A stress-induced early innate response causes multidrug tolerance in melanoma

Abstract: Acquired drug resistance constitutes a major challenge for effective cancer therapies with melanoma being no exception. The dynamics leading to permanent resistance are poorly understood but are important to design better treatments. Here we show that drug exposure, hypoxia or nutrient starvation leads to an early innate cell response in melanoma cells resulting in multidrug resistance, termed induced drug-tolerant cells (IDTCs). Transition into the IDTC state seems to be an inherent stress reaction for surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
116
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 35 publications
13
116
0
Order By: Relevance
“…However, Cheli et al described CD271 as an imperfect CSC marker since only the slow growing cells among the CD271 + subpopulation presented increased tumorigenic potential (40). Our results support those of Ravindran Menon et al (41), who demonstrated that PLX4032 increased CD271 expression in CM cells and induced the transition into a slow cycling state. The same phenotype was also observed when cells were exposed to different types of stress, such as hypoxia or nutrient starvation, and the authors proposed that these changes were part of an early innate response program.…”
Section: Discussionsupporting
confidence: 92%
“…However, Cheli et al described CD271 as an imperfect CSC marker since only the slow growing cells among the CD271 + subpopulation presented increased tumorigenic potential (40). Our results support those of Ravindran Menon et al (41), who demonstrated that PLX4032 increased CD271 expression in CM cells and induced the transition into a slow cycling state. The same phenotype was also observed when cells were exposed to different types of stress, such as hypoxia or nutrient starvation, and the authors proposed that these changes were part of an early innate response program.…”
Section: Discussionsupporting
confidence: 92%
“…The acquisition of transiently heritable states in drug‐treated melanoma cells is reminiscent of reversible drug tolerance previously shown to involve chromatin modifications sensitive to HDAC inhibition (Sharma et al , ; Ravindran Menon et al , ). We therefore performed a focused screen with a library of small‐molecule inhibitors of epigenome‐modifying enzymes to identify those that reduced NGFR induction by vemurafenib.…”
Section: Resultsmentioning
confidence: 99%
“…qRT-PCR was performed as described previously (7) using gene-specific primers (Supplementary Table S3). The qPCR array (PAHS-090Z, Qiagen) was performed according to the manufacturer’s protocol using mRNA extracted from WM9.…”
Section: Methodsmentioning
confidence: 99%